Grammar by thefable. Or: Thefableby grammar - De Moura Neves, María Helena [UNESP] (My University, 2014)
With the purpose of analyzing the function developed byt the fable, this paper begins with its definition, historically linked to the rhetorical art, the teaching force and the literary value, to reach a grammatical analysis of the narrative structure in which genre is presented. From the functionalist point of view, the function determines thestructure, and, accordingly, this study shows the fable resolved in specific modes of activation of the utterance formation basic processes such as the establishment of predications and the creation of the referential network of its participants. Since the beginning, the discursive activation of properties is crucial, which, working toward specific goals, configure linguistic characteristics that define the specific nature of the fable.
A gramáticapelafábula. Ou: Afábulapelagramática
Keywords: Fable; Functionalism; Grammar